Evaluation of Aqueous and Ethanolic Extraction for Coriander Seeds, Leaves and Stems and Studying their Antibacterial Activity - Oudah, Intisar; ali, Yasmine (Iraqi National Journal of Nursing Specialties, 2010)
Objective: To evaluate two kinds of extraction (aqueous and ethanolic) for coriander using seeds, leaves and stems andstudying their antibacterial activity against nine different microorganisms.Methodology: Coriander was selected to carry out this study. Seeds, leaves and stems were collected from local markets inBaghdad then dried in shade for at least 10 days and grinded to fine powder. Aqueous hot extracts for 1hr. at (50c) andcold extracts for 24 hrs at (4c) were performed by using seeds, leaves and stems then studied antibacterial effect againstnine different microorganisms by using well diffusion technique. Cold aqueous extracts of coriander seeds for 48 hrs. and72 hrs and ethanolic extraction for 48hrs of seed, leaves and stems also performed.Results: This study showed that hot aqueous extracts for 1hr. to all parts of coriander indicated no antibacterial activity,while cold aqueous extract for 24hrs of coriander seeds had inhibitory effect for some tested bacteria, but leaves and stemshad not. Cold aqueous extract of seeds for 48hrs showed antibacterial activity for all tested bacteria but in 72hrs there wasno inhibitory effect. On the other hand, ethanolic extracts of seeds, leaves and stems for 48hrs had antibacterial activity andthe highest values for inhibition zone shown in Klebsiella pneumoniae and Proteus mirabilis.Recommendations: The study recommends using coriander seeds extract as alternative medical therapy formicroorganisms which may resist conventional treatment. This study is a first step for further studies. It is necessary to usevarious extraction methods to give active materials with high percentage, although different organic solvents to be usedwith coriander plant to obtain extracts used for testing different kinds of microorganisms which have highly resistance toconventional treatment.